An Effective Amperometric Biosensor Based on Gold Nanoelectrode Arrays - Zhu Yingchun; Zeng Yi; Xu Fangfang; Liu Yanyan (Nanoscale Research Letters, 2008)
Abstract A sensitive amperometric biosensor based on gold nanoelectrode array (NEA) was investigated. The gold nanoelectrode array was fabricated by template-assisted electrodeposition on general electrodes, which shows an ordered well-defined 3D structure of nanowires. The sensitivity of the gold NEA to hydrogen peroxide is 37 times higher than that of the conventional electrode. The linear range of the platinum NEA toward H2O2is from 1 × 10−6to 1 × 10−2 M, covering four orders of magnitudes with detection limit of 1 × 10−7 M and a single noise ratio (S/N) of four. The enzyme electrode exhibits an excellent response performance to glucose with linear range from 1 × 10−5to 1 × 10−2 M and a fast response time within 8 s. The Michaelis–Menten constantkm and the maximum current densityi maxof the enzyme electrode were 4.97 mM and 84.60 μA cm−2, respectively. This special nanoelectrode may find potential application in other biosensors based on amperometric signals.